DNA replication origins in Haloferax volcanii - Hawkins, Michelle (2009)
DNA replication is fundamental to the proliferation of life. Sites of DNA replication initiation are called replication origins. Bacteria replicate from a single origin whereas eukaryotes utilise multiple origins for each chromosome. The archaeal domain includes species which replicate using multiple origins of replication in addition to those which use a single origin. Archaeal DNA replication proteins are similar to eukaryotic replication machinery. Most characterised archaeal origins are adjacent to an orc gene which encodes a homologue of the Orc1 subunit of the eukaryotic initiator protein complex.